Creating Machinima (3D) and Real Life Videos in an ESP Classroom (2018)
This research paper reports on the development of oral presentation skills in a 3D virtual world called Moviestorm machinima, in contrast with real-life videos. In this way, the implementation of both types of videos sought to promote the improvement of oral communication skills, specifically oral presentations in a foreign language, as well as promoting collaborative work. The study involved 60 students from different semesters of a private Colombian university from the schools of electronic engineering, computer science, and law, focusing on English for specific purposes. The results showed how students from different faculties worked collaboratively to achieve one goal: improve their oral presentation skills.